Teacher representation in news reporting on standardised testing: A case study from Western Australia - Shine, Kathryn; O'Donoghue, T. (Routledge Taylor and Francis Group, 2013)
News media coverage on education plays a “uniquely important role in shaping public opinion”, can influence educational policy, and can affect and concern teachers. Yet, research examining how teachers have been represented in the news is scarce. What is particularly scarce are investigations with a historical dimension. The study reported in this paper is offered as a contribution towards rectifying the deficit and pointing the way towards one of a number of avenues of research that other scholars in the field could take for various contexts (including different countries) and time periods. It is part of a much larger study whose aim was to provide a historical analysis of The West Australian newspaper’s representation of teachers in its reporting of five major educational developments in the State of Western Australia that were the subject of sustained coverage at various times between 1987 and 2007. The specific topic which is the focus of the analysis presented in this paper is “standardized testing”.